The Relationship between Teacher–Student Rapport and Willingness to Communicate among Iraqi EFL Learners: A Mixed-Method Study - Afzali Shahri, Mohammad; Salimi, Mahmood (Assessment and Practice in Educational Sciences, 2026)
Creating positive rapport between teachers and students is now considered to be a significant affective component of foreign language acquisition, particularly in a student-centered environment with an oral language focus, where students’ willingness to communicate (WTC) is substantially based on the quality of the relationship between the teacher and students in the classroom. However, little attention has been directed toward the role of rapport in fostering WTC in the context of Iraqi students studying English as a foreign language (EFL), where traditional, teacher-centered methodologies are prevalent. In this mixed methods study, we examined the relationship between rapport and WTC of Iraqi EFL undergraduate students. Quantitative data were obtained with standardized measures of rapport and WTC, while qualitative data were collected from semi-structured interviews and classroom observations to gain insight into how students perceive teachers’ classroom behaviors to influence their willingness to speak. The quantitative analysis demonstrated that students generally had a positive rapport with teachers and a moderate WTC, as well as a strong positive relationship between the two constructs. Qualitatively, the findings corroborated the positive relationship between rapport and WTC by clearly indicating that students’ communicative confidence and willingness to participate are enhanced through teachers demonstrating supportive, empathetic, and encouraging behaviors, especially those that reduce anxiety and fear of negative evaluation. This study emphasizes that the relational and affective dimensions of teaching are crucial to developing WTC in Iraqi EFL classrooms, and proposes directions for future research and pedagogical implications.